2019
DOI: 10.1155/2019/6756352
|View full text |Cite
|
Sign up to set email alerts
|

Severe ARDS Complicating an Acute Intentional Cresol Poisoning

Abstract: Cresol is a phenol derivative used as a disinfectant that may cause gastrointestinal corrosive injury, central nervous system, cardiovascular disturbances, renal, and hepatic injury following intoxication. We present a case of a female patient who was admitted to the emergency department after ingesting an unknown amount of cresol; she was admitted with tachypnea, shortness of breath with low oxygen level in the blood. She did not develop hepatic or renal dysfunction. The gastrointestinal endoscopy was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…o-Cresol is a methyl-substituted phenol at the ortho position and is found in cigarette smoke [ 83 , 84 ]. It is considered toxic and has been associated with acute respiratory distress syndrome along with cardiovascular, renal, and hepatic pathology following inhalation exposures [ 85 ]. In the current study, o-Cresol significantly impaired ADP-stimulated skeletal muscle mitochondrial respiration fueled by pyruvate/malate alone, as well as pyruvate/malate and succinate together.…”
Section: Discussionmentioning
confidence: 99%
“…o-Cresol is a methyl-substituted phenol at the ortho position and is found in cigarette smoke [ 83 , 84 ]. It is considered toxic and has been associated with acute respiratory distress syndrome along with cardiovascular, renal, and hepatic pathology following inhalation exposures [ 85 ]. In the current study, o-Cresol significantly impaired ADP-stimulated skeletal muscle mitochondrial respiration fueled by pyruvate/malate alone, as well as pyruvate/malate and succinate together.…”
Section: Discussionmentioning
confidence: 99%
“…We report that phenol and cresol intoxication can be responsible for respiratory failure with acute respiratory distress syndrome (ARDS) [5] found in 3 patients included in our series. Cresol intoxication can also lead to bronchospasm with pulmonary edema in poisoned patients [10] which may explain the clinical presentation of patient C. T. Hashimoto et al [11] reported the increase of aminotransferase levels after cresol ingestion evoking probable hepato-cellular injury that can manifest even after a 24-hour asymptomatic period explaining the late onset of liver failure in patient D who had an initially normal hepatic function and presented 24 hours later a high transaminases level.…”
Section: Discussionmentioning
confidence: 99%